Accounting and Marketing Training and Assistance on MSME Wall Panel: Pelatihan dan Pendampingan Akuntansi dan Pemasaran pada UMKM Wall Panel - Hariyanto, Wiwit; Yani, M; Dewi, Santi Rahma (Universitas Muhammadiyah Sidoarjo, 2022)
Wall panel products are handicraft products that are still rare in the market. The target market for this business are hotels, the tourism sector, and large companies. Meanwhile, the MSME Wall Panel is still having difficulty determining the selling price and effective marketing. The purpose of this community service is to increase knowledge and skills in the field of accounting and marketing at the MSME Wall Panel. The implementation method used is socialization, training and mentoring. The results obtained are that the MSME Wall panel is now in determining the cost of production, cost of goods sold, selling price and marketing both offline and online. The impact of the training and mentoring is that the MSME Wall Panel can independently determine a reasonable and appropriate selling price and can do offline and online marketing.Wall panel products are handicraft products that are still rare in the market. The target market for this business are hotels, the tourism sector, and large companies. Meanwhile, the MSME Wall Panel is still having difficulty determining the selling price and effective marketing. The purpose of this community service is to increase knowledge and skills in the field of accounting and marketing at the MSME Wall Panel. The implementation method used is socialization, training and mentoring. The results obtained are that the MSME Wall panel is now in determining the cost of production, cost of goods sold, selling price and marketing both offline and online. The impact of the training and mentoring is that the MSME Wall Panel can independently determine a reasonable and appropriate selling price and can do offline and online marketing.